PENGELOLAAN DANA MASJID DI KOTA AMBON (Studi Terhadap Fungsi Sosial Masjid An-Nur Batu Merah dan Masjid Al-Ukhuwah Kapaha) - Rosita Tehuayo (IAIN Ambon, 2021)
This research aims to find out fund management of An-Nur mosque in Batu Merah village and Al-Ukhuwah Kapaha Mosque and to find out the relation of fund management of An-Nur mosque in Batu Merah village and Al-Ukhuwah Mosque in Kapaha, and social functions of both mosques. This type of research is field research with a case study approach qualitative. This research is focused on the case of